Bimetal anionic ring-opening polymerization catalyst, preparation method and application of bimetallic anionic ring-opening polymerization catalyst in preparation of fluorosilicone rubber with controllable molecular weight
The bimetallic anion ring-opening polymerization catalyst addresses molecular weight control issues in fluorosilicone rubber production by creating a bimetallic active center that inhibits side reactions, resulting in high-quality, controllable molecular weight fluorosilicone rubber with narrow distribution, suitable for large-scale production.
Patent Information
- Application Number
- CN202411580322.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-11-07
AI Technical Summary
Existing fluorosilicone rubber production methods face challenges in controlling molecular weight and molecular weight distribution due to side reactions during anionic ring-opening polymerization, leading to low molecular weight polymers and uneven quality, which are exacerbated by the strong electrophilicity of fluorine-containing side groups.
A bimetallic anion ring-opening polymerization catalyst is prepared by combining an alkali metal compound with a cyclosiloxane and a compound of the form MtRn, followed by a promoter, to create a bimetallic active center with controlled steric hindrance and alkalinity, inhibiting side reactions and allowing for precise molecular weight adjustment.
The method achieves controllable molecular weight fluorosilicone rubber with narrow molecular weight distribution, eliminating the need for additional neutralization steps and ensuring high stability and quality, suitable for large-scale production.
Smart Images

Figure CN119219922A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of catalysts for preparing fluorosilicone rubber, and relates to a catalyst composition suitable for anionic ring-opening polymerization of cyclosiloxane monomers, a preparation method, and a stable, industrially applicable preparation process for controllable molecular weight fluorosilicone rubber raw rubber, and in particular to a preparation method for a class of bimetallic anionic ring-opening polymerization catalysts and their application in the preparation of controllable molecular weight fluorosilicone rubber. Technical Background
[0002] The main chain structure of fluorosilicone rubber is mainly composed of -Si-O- repeating units with high flexibility and high bond energy, which gives it excellent high and low temperature resistance. The side chain is composed of trifluoropropyl (-CH2-CH2-CF3) and methyl (-CH3), and the fluorine-containing substituent significantly improves the material's tolerance to oils and solvents. Fluorosilicone rubber can therefore remain stable in extreme temperature conditions (-55℃~230℃) and oily environments. Its application areas include national defense and military industry, aerospace, deep-sea exploration, automobiles and petrochemicals, etc. It is one of the synthetic rubbers with the best comprehensive performance in the world.
[0003] In the production process of fluorosilicone rubber, the control of molecular weight is crucial, which directly affects the mechanical properties of the rubber and the quality of the final product. The catalysts commonly used in the preparation process, such as alkali metal hydroxides, quaternary ammonium hydroxides and quaternary phosphonium hydroxides, are all strongly alkaline. The strong electronic attraction of the fluorine side group increases the electrophilicity of the silicone bond, which triggers the "bite-back" within the molecule and the chain transfer side reaction between molecules during the polymerization process, resulting in a decrease in molecular weight and uneven distribution, and then generating a large amount of low molecular weight polymers. For example, when potassium hydroxide is used to perform bulk ring-opening polymerization on 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane (D3F), the average content of the ring body at the polymerization equilibrium state can be as high as 86.5% (Journal of Polymer Science Polymer Letter Edition, 1965, 3, 473-482).
[0004] To solve these problems, two main strategies are currently used. The first is to change the catalytic system, such as using less active butyl lithium as a catalyst and using dimethyl sulfoxide as a promoter to effectively inhibit the "backbite" reaction, thereby reducing the content of the ring body at the polymerization equilibrium (Journal of Polymer Science Part A, 1989, 27 (4), 1241-1258). Although the side reactions can be reduced to a certain extent by adjusting the auxiliary agent and the catalyst, the occurrence of side reactions has not been completely inhibited, which may eventually affect the quality of fluorosilicone rubber. The second is to control the polymerization reaction time and terminate the reaction when the yield of the linear polymer is the highest (CN 114381001 A). This requires higher control over the polymerization process and equipment, and may also lead to a decrease in the stability of the product batch. In addition, at the end of the polymerization, the problem of catalyst neutralization must be solved. The residual catalyst may attack the silicone bond in the polymer chain, resulting in chain breakage. In view of the high viscosity and excellent oil and chemical resistance of high molecular weight fluorosilicone rubber, the addition and effective dispersion of neutralizers are particularly difficult. Therefore, special measures must be taken during the preparation process to ensure the high performance and safety of the product. Summary of the invention
[0005] The present invention aims to solve the shortcomings of the existing fluorinated cyclosiloxane anion ring-opening polymerization catalytic technology and provide a method for preparing a bimetallic anion ring-opening polymerization catalyst. By using the prepared bimetallic anion ring-opening polymerization catalyst to carry out bulk polymerization of fluorinated siloxane, a fluorosilicone rubber with controllable molecular weight, narrow molecular weight distribution and excellent stability can be prepared. Compared with the prior art, the method has the advantages of simple operation, strong controllability, etc., and is very suitable for large-scale production.
[0006] In order to achieve the above object, the technical solution of the present invention is:
[0007] A method for preparing a bimetallic anion ring-opening polymerization catalyst comprises the following steps:
[0008] Step (1) Under the protection of inert gas, an alkali metal compound and a cyclosiloxane are added to a preparation kettle in sequence, and aged at 60-210 degrees Celsius for 30-600 minutes to form a homogeneous transparent solution; in this step, the alkali metal compound and the cyclosiloxane react fully to reach a thermodynamic equilibrium state, generating an oxygen anion active center, and the counter ion is the corresponding alkali metal cation used.
[0009] Step (2) adding a compound having a general structural formula of MtR n The compound is aged at 0-60 degrees Celsius for 5-120 minutes to form a homogeneous transparent solution; in this step, MtR nThe compound cooperates with the above-mentioned oxygen anion terminal to form a bimetallic active center, which has greater steric hindrance and weakened alkalinity than the active center prepared in step (1), thereby achieving the goal of inhibiting the "backbiting" side reaction of the active center to the polymer.
[0010] Step (3) adding a promoter to the solution obtained in step (2), and preparing a bimetallic anionic ring-opening polymerization catalyst after sufficient mixing; in this step, the addition of promoters of different types and polarities can effectively regulate the alkalinity of the anionic active center, thereby adapting to the difference in polymerization activity caused by cyclosiloxanes of different structures to obtain the target copolymerized fluorosilicone rubber.
[0011] In the bimetallic anion ring-opening polymerization catalyst, the alkali metal compound, cyclosiloxane, MtR n The molar ratio of the promoter is 1:(2–10):(0.1–2):(2–1000), wherein the concentration of the alkali metal element is 0.05–1.6 mmol / g.
[0012] The general structural formula of step (2) is MtR n In the compound, Mt is selected from metal magnesium, zinc or aluminum; R is selected from methyl, ethyl, isopropyl, n-butyl, isobutyl or n-octyl, phenyl; the value of n corresponds to the type of Mt, if Mt is magnesium or zinc, then n is 2; if Mt is aluminum, then n is 3.
[0013] The alkali metal compound is selected from lithium hydroxide, sodium hydroxide, potassium hydroxide, lithium tert-butoxide, sodium tert-butoxide, potassium tert-butoxide, n-butyl lithium, sec-butyl lithium, and tert-butyl lithium.
[0014] The cyclosiloxane is selected from hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, and 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane.
[0015] The accelerator is at least one of acetonitrile, dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, pyridine, acetone, 1,4-dioxane, methyl pyrrolidone, phosphazene base, tetrahydrofuran, methyl formate, ethyl acetate, toluene, diethylene glycol dimethyl ether, and ethylene glycol dimethyl ether.
[0016] A type of bimetallic anion ring-opening polymerization catalyst is obtained by adopting the above preparation method.
[0017] A type of bimetallic anion ring-opening polymerization catalyst is used to prepare fluorosilicone rubber with controllable molecular weight. The preparation method comprises the following steps:
[0018] (1) Add 1,3,5-trimethyl-1,3,5-tri(3,3,3-trifluoropropyl)cyclotrisiloxane and cyclosiloxane monomers into a polymerization reactor, heat and evacuate to dehydrate; wherein the cyclosiloxane accounts for 0.5%-15% of the total monomers.
[0019] (2) Adding a bimetallic anion ring-opening polymerization catalyst into a polymerization reactor, wherein the molar ratio of the bimetallic anion ring-opening polymerization catalyst to the monomer is 100-20000, heating to 60-120 degrees Celsius to start the polymerization reaction, and polymerizing for 10-600 minutes to prepare fluorosilicone rubber.
[0020] The cyclosiloxane monomer is selected from one or more of hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane, and 2,4,6-triphenyl-2,4,6-trimethylcyclotrisiloxane.
[0021] The fluorosilicone rubber prepared by the above-mentioned preparation method also belongs to the protection scope of the present invention;
[0022] The structure of the fluorosilicone rubber is shown in formula (I):
[0023]
[0024] Wherein, X is one or more of methyl, phenyl and vinyl, preferably methyl and vinyl;
[0025] The molecular weight of the fluorosilicone rubber is 0.2-2.5 million, and the molecular weight distribution is less than 1.25.
[0026] Beneficial effects of the present invention:
[0027] (1) In the preparation process of the bimetallic anion ring-opening catalyst of the present invention: The preparation process of the bimetallic anion ring-opening catalyst involves adding a metal compound of the MtRn structure to a traditional catalyst. By precisely controlling the volume of the R structure in the compound and the properties of the Mt metal, the present method can effectively control the steric hindrance and alkalinity around the oxygen anion active center. This strategy not only suppresses the common "backbite" side reaction in siloxane polymerization, but also adapts to the copolymerization of different active ring siloxanes by finely controlling the alkalinity of the anion active center, thereby expanding the synthesis method of the polymer chain structure of fluorosilicone rubber materials.
[0028] (2) During the application of the bimetallic anion ring-opening catalyst of the present invention: The bimetallic anion ring-opening catalyst used in the present invention exhibits a beneficial ring-opening polymerization effect on 1,3,5-trimethyl-1,3,5-tri(3,3,3-trifluoropropyl)cyclotrisiloxane. Compared with existing catalysts, this catalytic system can effectively adjust the molecular weight of the resulting fluorosilicone rubber by controlling the amount of catalyst, and ensure that its molecular weight distribution is narrow and no small molecule ring structure is produced. In addition, the use of this catalytic system does not require an additional neutralization process to maintain the good storage stability of fluorosilicone rubber. The invention provides a reliable base rubber for the manufacture of high-strength fluorosilicone rubber products. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The hydrogen nuclear magnetic spectra of the bimetallic anion ring-opening polymerization catalysts prepared in Example 13 (A) and Example 16 (B) of the present invention;
[0030] Figure 2 This is the NMR lithium spectrum of the bimetallic anion ring-opening polymerization catalyst prepared in Example 13 of the present invention;
[0031] Figure 3 This is the H-NMR spectrum of the fluorosilicone rubber prepared in Example 35 of the present invention;
[0032] Figure 4 Gel permeation chromatogram of fluorosilicone rubber prepared in Example 31 (dashed line) and Example 32 (solid line) of the present invention. DETAILED DESCRIPTION
[0033] The technical solution of the present invention is further described below in conjunction with embodiments.
[0034] Examples 1-28 are preparation methods of bimetallic anion ring-opening polymerization catalysts.
[0035] Example 1
[0036] 0.51 g of lithium hydroxide (21.35 mmol) was added to a 500 ml reactor. 9.50 g of D3 (42.70 mmol) was added at room temperature and stirred thoroughly. Afterwards, the temperature was gradually raised to 60 degrees Celsius and maintained for 30 minutes. Then 2.14 ml (2.14 mmol) of triethylaluminum in hexane (1.0 mol / L) was added and the reaction was continued at 0 degrees Celsius for 120 minutes. Finally, 1.75 g of acetonitrile (0.043 mol) was added, stirred well and stored in a desiccator for later use. By titration, the alkali metal concentration in the catalyst was measured to be 1.6156 mmol / g.
[0037] Example 2
[0038] 0.08 g of lithium hydroxide (3.33 mmol) was added to a 500 ml reactor. 5.93 g of D4 (20.00 mmol) was added at room temperature and stirred thoroughly. Afterwards, the temperature was gradually raised to 135 degrees Celsius and maintained for 300 minutes. Then 3.33 ml (3.33 mmol) of triisobutylaluminum in hexane (1.0 mol / L) was added and reacted at 30 degrees Celsius for 60 minutes. Finally, 130.22 g of dimethyl sulfoxide (1.667 mol) was added, stirred well and stored in a desiccator for later use. By titration, the alkali metal concentration in the catalyst was measured to be 0.0241 mmol / g.
[0039] Example 3
[0040] 0.05 g of lithium hydroxide (2.00 mmol) was added to a 500 ml reactor. 9.37 g of D3F (20.00 mmol) was added at room temperature and stirred thoroughly. Afterwards, the temperature was gradually raised to 210 degrees Celsius and maintained for 600 minutes. Then 4.00 ml (4.00 mmol) of a hexane solution of di-n-butyl magnesium (1.0 mol / L) was added and reacted at 60 degrees Celsius for 30 minutes. Finally, 146.18 g of N,N-dimethylformamide (2.000 mol) was added, stirred well and stored in a desiccator for later use. By titration, the alkali metal concentration in the catalyst was measured to be 0.0126 mmol / g.
[0041] Example 4
[0042] 2.67 g of sodium hydroxide (66.67 mmol) was added to a 500 ml reactor. 88.98 g of D3 (400.00 mmol) was added at room temperature and stirred thoroughly. Afterwards, the temperature was gradually raised to 135 degrees Celsius and maintained for 30 minutes. Then 133.33 ml (133.33 mmol) of a hexane solution of diethylzinc (1.0 mol / L) was added and reacted at 60 degrees Celsius for 0 minutes. Finally, 11.62 g of N,N-dimethylacetamide (0.133 mol) was added, stirred well and stored in a desiccator for later use. By titration, the alkali metal concentration in the catalyst was measured to be 0.3438 mmol / g.
[0043] Example 5
[0044] 0.17 g of sodium hydroxide (4.27 mmol) was added to a 500 ml reactor. 12.67 g of D4 (42.70 mmol) was added at room temperature and stirred thoroughly. Afterwards, the temperature was gradually raised to 210 degrees Celsius and maintained for 300 minutes. Then 0.43 ml (0.43 mmol) of a hexane solution of dioctyl zinc (1.0 mol / L) was added and reacted at 0 degrees Celsius for 60 minutes. Finally, 168.88 g of pyridine (2.135 mol) was added, stirred well and stored in a desiccator for later use. By titration, the alkali metal concentration in the catalyst was measured to be 0.0235 mmol / g.
[0045] Example 6
[0046] Add 0.06 g of sodium hydroxide (1.50 mmol) to a 500 ml reactor. Add 1.41 g of D3F (3.00 mmol) at room temperature and stir thoroughly. After that, gradually heat up to 60 degrees Celsius and maintain for 600 minutes. Then add 1.50 ml (1.50 mmol) of diphenyl magnesium in hexane solution (1.0 mol / L) and react at 30 degrees Celsius for 5 minutes. Finally, add 132.17 g of 1,4-dioxane (1.500 mol), stir well and store it in a desiccator for use. By titration, the alkali metal concentration in the catalyst was measured to be 0.0111 mmol / g.
[0047] Example 7
[0048] 2.24 g potassium hydroxide (40.00 mmol) was added to a 500 ml reactor. 88.98 g D3 (400.00 mmol) was added at room temperature and stirred thoroughly. Afterwards, the temperature was gradually raised to 210 degrees Celsius and maintained for 600 minutes. Then 80.00 ml (80.00 mmol) of triethylaluminum in hexane (1.0 mol / L) was added and reacted at 30 degrees Celsius for 60 minutes. Finally, 7.93 g methyl pyrrolidone (0.080 mol) was added, stirred well and stored in a desiccator for later use. By titration, the alkali metal concentration in the catalyst was measured to be 0.2605 mmol / g.
[0049] Example 8
[0050] 0.04 g potassium hydroxide (0.75 mmol) was added to a 500 ml reactor. 0.44 g D4 (1.50 mmol) was added at room temperature and stirred thoroughly. Afterwards, the temperature was gradually raised to 60 degrees Celsius and maintained for 30 minutes. Then 0.08 ml (0.08 mmol) of a hexane solution of triisobutylaluminum (1.0 mol / L) was added and reacted at 60 degrees Celsius for 5 minutes. Finally, 180.23 g phosphazene base (0.375 mol) was added and stirred well and stored in a desiccator for use. By titration, the alkali metal concentration in the catalyst was measured to be 0.0041 mmol / g.
[0051] Example 9
[0052] 0.14 g potassium hydroxide (2.50 mmol) was added to a 500 ml reactor. 7.03 g D3F (15.00 mmol) was added at room temperature and stirred thoroughly. Afterwards, the temperature was gradually raised to 135 degrees Celsius and maintained for 300 minutes. Then 2.50 ml (2.50 mmol) of a hexane solution of di-n-butyl magnesium (1.0 mol / L) was added and reacted at 0 degrees Celsius for 120 minutes. Finally, 180.28 g tetrahydrofuran (2.500 mol) was added, stirred well and stored in a desiccator for later use. By titration, the alkali metal concentration in the catalyst was measured to be 0.0132 mmol / g.
[0053] Example 10
[0054] 0.44 g of lithium tert-butoxide (5.50 mmol) was added to a 500 ml reactor. 2.45 g of D3 (11.00 mmol) was added at room temperature and stirred thoroughly. Afterwards, the temperature was gradually raised to 60 degrees Celsius and maintained for 300 minutes. Then 11.00 ml (11.00 mmol) of a hexane solution of diethyl zinc (1.0 mol / L) was added and reacted at 30 degrees Celsius for 120 minutes. Finally, 165.14 g of methyl formate (2.750 mol) was added and stirred well and stored in a desiccator for use. By titration, the alkali metal concentration in the catalyst was measured to be 0.0313 mmol / g.
[0055] Embodiment 11
[0056] 0.17 g of lithium tert-butoxide (2.17 mmol) was added to a 500 ml reactor. 3.86 g of D4 (13.00 mmol) was added at room temperature and stirred thoroughly. Afterwards, the temperature was gradually raised to 135 degrees Celsius and maintained for 600 minutes. Then 0.22 ml (0.22 mmol) of a hexane solution of dioctyl zinc (1.0 mol / L) was added and reacted at 60 degrees Celsius for 5 minutes. Finally, 190.91 g of ethyl acetate (2.167 mol) was added, stirred well and stored in a desiccator for later use. By titration, the alkali metal concentration in the catalyst was measured to be 0.0111 mmol / g.
[0057] Example 12
[0058] 2.40 grams of lithium tert-butoxide (30.00 mmol) are added to a 500 ml reactor. 140.56 grams of D3F (300.00 mmol) are added at room temperature and stirred thoroughly. Afterwards, the mixture is gradually heated to 210 degrees Celsius and maintained for 30 minutes. Then 30.00 milliliters (30.00 mmol) of a hexane solution of diphenyl magnesium (1.0 mol / L) are added and reacted at 0 degrees Celsius for 60 minutes. Finally, 8.05 grams of dimethyl sulfoxide (0.060 mol) are added and stirred and stored in a desiccator for standby use. By titration, it is determined that the alkali metal concentration in the catalyst is 0.1750 mmol / g.
[0059] Example 13
[0060] 2.00 g of lithium tert-butoxide (25.00 mmol) was added to a 500 ml reactor. 46.85 g of D3F (100.00 mmol) was added at room temperature and stirred thoroughly. Afterwards, the temperature was gradually raised to 210 degrees Celsius and maintained for 600 minutes. Then 12.50 ml (12.50 mmol) of a hexane solution of triethylaluminum (1.0 mol / L) was added and reacted at 30 degrees Celsius for 30 minutes. Finally, 97.66 g of dimethyl sulfoxide (1.250 mol) was added, stirred well and stored in a desiccator for later use. By titration, the alkali metal concentration in the catalyst was measured to be 0.1613 mmol / g.
[0061] Embodiment 14
[0062] 0.40 g of sodium tert-butoxide (4.17 mmol) was added to a 500 ml reactor. 5.56 g of D3 (25.00 mmol) was added at room temperature and stirred thoroughly. Afterwards, the mixture was gradually heated to 210 degrees Celsius and maintained for 300 minutes. 0.42 ml (0.42 mmol) of a hexane solution of triethylaluminum (1.0 mol / L) was then added and reacted at 60 degrees Celsius for 60 minutes. Finally, 187.75 g of diethylene glycol dimethyl ether (2.083 mol) was added and stirred and stored in a desiccator for standby use. By titration, the alkali metal concentration in the catalyst was 0.0215 mmol / g.
[0063] Embodiment 15
[0064] 0.19 g of sodium tert-butoxide (2.00 mmoles) was added to a 500 ml reactor. 5.93 g of D4 (20.00 mmoles) was added at room temperature and stirred thoroughly. Afterwards, the mixture was gradually heated to 60 degrees Celsius and maintained for 600 minutes. 4.00 ml (4.00 mmoles) of a hexane solution of triisobutylaluminum (1.0 mol / L) were then added and reacted at 0 degrees Celsius for 120 minutes. Finally, 180.24 g of ethylene glycol dimethyl ether (2.000 mol) was added and stirred and stored in a desiccator for standby use. By titration, the alkali metal concentration in the catalyst was 0.0106 mmol / g.
[0065] Example 16
[0066] 10.09 g of sodium tert-butoxide (105.00 mmol) was added to a 500 ml reactor. 98.39 g of D3F (210.00 mmol) was added at room temperature and stirred thoroughly. Afterwards, the temperature was gradually raised to 135 degrees Celsius and maintained for 30 minutes. Then 105.00 ml (105.00 mmol) of a hexane solution of di-n-butyl magnesium (1.0 mol / L) was added and reacted at 30 degrees Celsius for 5 minutes. Finally, 8.62 g of acetonitrile (0.210 mol) was added and stirred well and stored in a desiccator for use. By titration, the alkali metal concentration in the catalyst was measured to be 0.5570 mmol / g.
[0067] Embodiment 17
[0068] 0.48 g of potassium tert-butoxide (4.27 mmol) was added to a 500 ml reactor. 9.50 g of D3 (42.70 mmol) was added at room temperature and stirred thoroughly. Afterwards, the temperature was gradually raised to 135 degrees Celsius and maintained for 600 minutes. Then 0.43 ml (0.43 mmol) of a hexane solution of diethyl zinc (1.0 mol / L) was added and reacted at 30 degrees Celsius for 120 minutes. Finally, 166.81 g of dimethyl sulfoxide (2.135 mol) was added, stirred well and stored in a desiccator for use. By titration, the alkali metal concentration in the catalyst was measured to be 0.0241 mmol / g.
[0069] Embodiment 18
[0070] 0.28 g of potassium tert-butoxide (2.50 mmol) was added to a 500 ml reactor. 4.45 g of D4 (15.00 mmol) was added at room temperature and stirred thoroughly. Afterwards, the temperature was gradually raised to 210 degrees Celsius and maintained for 30 minutes. Then 2.50 ml (2.50 mmol) of a hexane solution of dioctyl zinc (1.0 mol / L) was added and reacted at 60 degrees Celsius for 5 minutes. Finally, 182.73 g of N,N-dimethylformamide (2.500 mol) was added, stirred well and stored in a desiccator for later use. By titration, the alkali metal concentration in the catalyst was measured to be 0.0132 mmol / g.
[0071] Embodiment 19
[0072] 8.42 g of potassium tert-butoxide (75.00 mmol) was added to a 500 ml reactor. 70.28 g of D3F (150.00 mmol) was added at room temperature and stirred thoroughly. Afterwards, the temperature was gradually raised to 60 degrees Celsius and maintained for 300 minutes. Then 150.00 ml (150.00 mmol) of a hexane solution of diphenyl magnesium (1.0 mol / L) was added and reacted at 0 degrees Celsius for 60 minutes. Finally, 13.07 g of N,N-dimethylacetamide (0.150 mol) was added and stirred well and stored in a desiccator for use. By titration, the alkali metal concentration in the catalyst was measured to be 0.3871 mmol / g.
[0073] Embodiment 20
[0074] 46.88 ml of n-butyl lithium (75.00 mmol) was added to a 500 ml reactor. 100.11 g of D3 (450.00 mmol) was added at room temperature and stirred thoroughly. Afterwards, the temperature was gradually raised to 60 degrees Celsius and maintained for 300 minutes. Then 75.00 ml (75.00 mmol) of triethylaluminum in hexane (1.0 mol / L) was added and reacted at 60 degrees Celsius for 5 minutes. Finally, 11.87 g of pyridine (0.150 mol) was added, stirred well and stored in a desiccator for later use. By titration, the alkali metal concentration in the catalyst was measured to be 0.3849 mmol / g.
[0075] Embodiment 21
[0076] Add 2.50 ml of n-butyl lithium (4.00 mmol) to a 500 ml reactor. Add 11.86 g of D4 (40.00 mmol) at room temperature and stir thoroughly. After that, gradually heat up to 135 degrees Celsius and maintain for 600 minutes. Then add 8.00 ml (8.00 mmol) of triisobutylaluminum hexane solution (1.0 mol / L) and react at 0 degrees Celsius for 60 minutes. Finally, add 176.22 g of 1,4-dioxane (2.000 mol), stir well and store in a desiccator for later use. By titration, the alkali metal concentration in the catalyst was measured to be 0.0205 mmol / g.
[0077] Embodiment 22
[0078] 1.19 ml of n-butyl lithium (1.90 mmol) was added to a 500 ml reactor. 1.78 g of D3F (3.80 mmol) was added at room temperature and stirred thoroughly. Afterwards, the temperature was gradually raised to 210 degrees Celsius and maintained for 30 minutes. Then 0.19 ml (0.19 mmol) of a hexane solution of di-n-butyl magnesium (1.0 mol / L) was added and reacted at 30 degrees Celsius for 120 minutes. Finally, 188.35 g of methyl pyrrolidone (1.900 mol) was added, stirred well and stored in a desiccator for later use. By titration, the alkali metal concentration in the catalyst was measured to be 0.0099 mmol / g.
[0079] Embodiment 23
[0080] 0.22 ml of sec-butyl lithium (0.28 mmol) was added to a 500 ml reactor. 0.38 g of D3 (1.70 mmol) was added at room temperature and stirred thoroughly. Afterwards, the temperature was gradually raised to 60 degrees Celsius and maintained for 600 minutes. Then 0.28 ml (0.28 mmol) of a hexane solution of diethyl zinc (1.0 mol / L) was added and reacted at 30 degrees Celsius for 60 minutes. Finally, 136.17 g of phosphazene base (0.283 mol) was added and stirred well and stored in a desiccator for use. By titration, the alkali metal concentration in the catalyst was measured to be 0.0021 mmol / g.
[0081] Embodiment 24
[0082] 28.46 ml of sec-butyl lithium (37.00 mmol) was added to a 500 ml reactor. 109.75 g of D4 (370.00 mmol) was added at room temperature and stirred thoroughly. Afterwards, the temperature was gradually raised to 135 degrees Celsius and maintained for 30 minutes. Then 74.00 ml (74.00 mmol) of a hexane solution of dioctyl zinc (1.0 mol / L) was added and reacted at 60 degrees Celsius for 120 minutes. Finally, 5.34 g of tetrahydrofuran (0.074 mol) was added, stirred well and stored in a desiccator for later use. By titration, the alkali metal concentration in the catalyst was measured to be 0.2003 mmol / g.
[0083] Embodiment 25
[0084] 3.85 ml of sec-butyl lithium (5.00 mmol) are added to a 500 ml reactor. 4.69 g of D3F (10.00 mmol) are added at room temperature and stirred thoroughly. Afterwards, the mixture is gradually heated to 210 degrees Celsius and maintained for 300 minutes. 0.50 ml (0.50 mmol) of a hexane solution of diphenyl magnesium (1.0 mol / L) is then added and reacted at 0 degrees Celsius for 5 minutes. Finally, 150.13 g of methyl formate (2.500 mol) is added and stirred and stored in a desiccator for standby use. By titration, it is found that the alkali metal concentration in the catalyst is 0.0317 mmol / g.
[0085] Embodiment 26
[0086] 50.00 ml of tert-butyl lithium (50.00 mmol) was added to a 500 ml reactor. 111.23 g of D3 (500.00 mmol) was added at room temperature and stirred thoroughly. Afterwards, the temperature was gradually raised to 210 degrees Celsius and maintained for 30 minutes. Then 50.00 ml (50.00 mmol) of triethylaluminum in hexane (1.0 mol / L) was added and reacted at 0 degrees Celsius for 120 minutes. Finally, 8.81 g of ethyl acetate (0.100 mol) was added, stirred well and stored in a desiccator for later use. By titration, the alkali metal concentration in the catalyst was measured to be 0.2659 mmol / g.
[0087] Embodiment 27
[0088] 2.85 ml of tert-butyl lithium (2.85 mmol) was added to a 500 ml reactor. 1.69 g of D4 (5.70 mmol) was added at room temperature and stirred thoroughly. Afterwards, the temperature was gradually raised to 60 degrees Celsius and maintained for 300 minutes. Then 5.70 ml (5.70 mmol) of a hexane solution of triisobutyl aluminum (1.0 mol / L) was added and reacted at 30 degrees Celsius for 5 minutes. Finally, 191.19 g of dimethyl sulfoxide (1.425 mol) was added, stirred well and stored in a desiccator for later use. By titration, the alkali metal concentration in the catalyst was measured to be 0.0143 mmol / g.
[0089] Embodiment 28
[0090] 1.83 ml of tert-butyl lithium (1.83 mmol) was added to a 500 ml reactor. 5.15 g of D3F (11.00 mmol) was added at room temperature and stirred thoroughly. Afterwards, the temperature was gradually raised to 135 degrees Celsius and maintained for 600 minutes. Then 0.18 ml (0.18 mmol) of a hexane solution of di-n-butyl magnesium (1.0 mol / L) was added and reacted at 60 degrees Celsius for 60 minutes. Finally, 165.22 g of diethylene glycol dimethyl ether (1.833 mol) was added and stirred and stored in a desiccator for use. By titration, the alkali metal concentration in the catalyst was measured to be 0.0107 mmol / g.
[0091] Example 29 (Comparative Example)
[0092] 2.00 g of lithium tert-butoxide (25.00 mmol) was added to a 500 ml reactor. 46.85 g of D3F (100.00 mmol) was added at room temperature and stirred thoroughly. Afterwards, the temperature was gradually raised to 210 degrees Celsius and maintained for 600 minutes. Finally, 97.66 g of dimethyl sulfoxide (1.250 mol) was added, stirred well and stored in a desiccator for later use. By titration, the alkali metal concentration in the catalyst was measured to be 0.1706 mmol / g.
[0093] Example 30 (Comparative Example)
[0094] 0.40 g of sodium tert-butoxide (4.17 mmol) was added to a 500 ml reactor. 5.56 g of D3 (25.00 mmol) was added at room temperature and stirred thoroughly. Afterwards, the mixture was gradually heated to 210 degrees Celsius and maintained for 300 minutes. Finally, 187.75 g of diethylene glycol dimethyl ether (2.083 mol) was added and stirred and stored in a desiccator for later use. By titration, the alkali metal concentration in the catalyst was 0.0215 mmol / g.
[0095] Examples 31-40 are examples of using the above catalysts to prepare fluorosilicone rubber.
[0096] The corresponding cyclosiloxane monomers in Table 1 were added into a 250 ml reactor and preheated to the specified polymerization temperature. The specified catalyst was added once and the polymerization was maintained for 1 hour before being taken out. The molecular weight and its distribution were determined by gel permeation chromatography. The corresponding results are listed in Table 1.
[0097]
[0098]
[0099] Note: a The catalyst corresponds to the catalyst prepared in the numbered examples; b D3F, D3, D4, D3 Vi 、D3 Ph They correspond to 1,3,5-trimethyl-1,3,5-tri(3,3,3-trifluoropropyl)cyclotrisiloxane, hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane, and 2,4,6-triphenyl-2,4,6-trimethylcyclotrisiloxane, respectively.
[0100] Examples 31-34, 35-36, 3
[0101] The structure of the fluorosilicone rubber of formula (1) prepared in Examples 31-40, wherein the repeating units of Examples 31-34 without the X substituent are homopolymerized products of fluorinated siloxane, the X substituent in Examples 34-37 is vinyl, the X substituent in Example 38 is phenyl, and the X substituent in Examples 39-40 is methyl.
[0102] The only difference between Example 31 and Comparative Example 32 is that triethylaluminum was added during the preparation of the catalyst used in Example 31, while triethylaluminum was not added during the preparation of the catalyst used in Comparative Example 32. Both examples used the same molar equivalent ratio D3F / Li=200 for catalytic polymerization. The molecular weight and distribution of the obtained fluorosilicone rubber material were measured by gel permeation chromatography. The data showed that Figure 4The results show that the fluorosilicone rubber material prepared in Example 31 can completely inhibit the generation of small molecular weight ring structures; while Comparative Example 32 does not contain triethylaluminum, which indicates that the addition of triethylaluminum can change the activity of the active center, so that the active center only attacks the silicone bonds in the cyclosiloxane monomer instead of the silicone bonds in the polymer chain, thereby completely inhibiting the side reactions in the polymerization process and obtaining a high-purity linear high molecular weight fluorosilicone rubber.
[0103] The above-described embodiments merely express the implementation methods of the present invention, but they cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A method for preparing a bimetallic anion ring-opening polymerization catalyst, characterized in that: The steps include: Step (1), under the protection of an inert gas, aging the alkali metal compound and the cyclosiloxane at 60-210 degrees Celsius for 30-600 minutes to form a homogeneous transparent solution; Step (2), adding a compound having a general structural formula of MtR n The compound was aged at 0-60°C for 5-120 minutes to form a homogeneous transparent solution; Step (3), adding a promoter to the solution obtained in step (2), and mixing thoroughly to prepare a bimetallic anion ring-opening polymerization catalyst.
2. The method for preparing a bimetallic anion ring-opening polymerization catalyst according to claim 1, characterized in that: In the bimetallic anion ring-opening polymerization catalyst, the alkali metal compound, cyclosiloxane, MtR n The molar ratio of the promoter is 1:(2–10):(0.1–2):(2–1000), wherein the concentration of the alkali metal element is 0.05–1.6 mmol / g.
3. The method for preparing a bimetallic anion ring-opening polymerization catalyst according to claim 1, characterized in that: The general structural formula of step (2) is MtR n In the compound, Mt is selected from metal magnesium, zinc or aluminum; R is selected from methyl, ethyl, isopropyl, n-butyl, isobutyl or n-octyl, phenyl; the value of n corresponds to the type of Mt, if Mt is magnesium or zinc, then n is 2; if Mt is aluminum, then n is 3.
4. The method for preparing a bimetallic anion ring-opening polymerization catalyst according to claim 1, characterized in that: The alkali metal compound is selected from lithium hydroxide, sodium hydroxide, potassium hydroxide, lithium tert-butoxide, sodium tert-butoxide, potassium tert-butoxide, n-butyl lithium, sec-butyl lithium, tert-butyl lithium; The cyclosiloxane is selected from hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, and 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane; The accelerator is at least one of acetonitrile, dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, pyridine, acetone, 1,4-dioxane, methyl pyrrolidone, phosphazene base, tetrahydrofuran, methyl formate, ethyl acetate, toluene, diethylene glycol dimethyl ether, and ethylene glycol dimethyl ether.
5. A bimetallic anion ring-opening polymerization catalyst, characterized in that: The preparation method is adopted according to any one of claims 1 to 4.
6. Application of a bimetallic anion ring-opening polymerization catalyst, characterized in that: The bimetallic anion ring-opening polymerization catalyst is used for preparing fluorosilicone rubber with controllable molecular weight.
7. The use of a bimetallic anion ring-opening polymerization catalyst according to claim 6, characterized in that: The method for preparing fluorosilicone rubber comprises the following steps: Step (1), adding 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane and cyclosiloxane monomer into a polymerization reaction kettle, heating and vacuuming for dehydration; Step (2), adding a bimetallic anion ring-opening polymerization catalyst into a polymerization reactor, wherein the molar ratio of the bimetallic anion ring-opening polymerization catalyst to the monomer is 100-20000, heating to 60-120 degrees Celsius to start the polymerization reaction, and polymerizing for 10-600 minutes to prepare fluorosilicone rubber.
8. The use of a bimetallic anion ring-opening polymerization catalyst according to claim 7, characterized in that: In step (1), the cyclosiloxane monomer accounts for 0.5% to 15% of the total weight of the monomers; In step (1), the cyclosiloxane monomer is selected from one or more of hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane, and 2,4,6-triphenyl-2,4,6-trimethylcyclotrisiloxane.
9. The use of a bimetallic anion ring-opening polymerization catalyst according to claim 7, characterized in that: The molecular weight of the fluorosilicone rubber is 0.2-2.5 million, and the molecular weight distribution is less than 1.25; The fluorosilicone rubber structure is as follows: Wherein, X is one or more of methyl, phenyl and vinyl.
10. Use of a bimetallic anion ring-opening polymerization catalyst according to claim 9, characterized in that: The X is methyl and vinyl.
Citation Information
Patent Citations
Method for preparing composite catalyst applied to alkylene oxide ring-expansion polymerization and use
CN101392053A
Preparation method and application of hydrolysis-resistant high-activity bimetallic titanium catalyst
CN118325048A
Catalyst composition and preparation method of fluorine silicon contained polymer
CN1724580A
Mixed-acid modified zinc-cobalt double metal cyanide catalyst and preparation method thereof
US20210213431A1